Class participation in politics in Southeast Asia - Capuno, Joseph J. (The Philippine Review of Economics, 2015)
Using the dataset from the Asian Barometer Survey conducted in 2010-2012, we determine the variations in political participation across socioeconomic classes in five Southeast Asian countries and apply Oaxaca decomposition method to explain the variations. In general, we find high rates of voting participation across classes in Indonesia, Malaysia, the Philippines, and Thailand. In Singapore, barely half of the sample voted in previous elections. In Indonesia, Thailand, and Malaysia, the middle classes distinguish themselves from the rest by participating in other political activities, including contacting officials or the news media, joining others to voice out or directly address their common concerns, and attending rallies or demonstrations.